BC Data ScoutTM: A New Tool To Investigate Datasets For Health Research - Kesselring, Sarah; Galo, Jessica; Sanderson, Kelly; Wong, Shirley; Neuman, Maureen; Mintha, Jim; McGrail, Kim (International Journal of Population Data Science, 2018)
Introduction BC’s Ministry of Health (MOH) maintains many administrative databases with rich information and analytical potential. Researchers are keen to use these data for both discovery and applied research. Historically, limited views of data availability and populations therein have supported study feasibility. Therefore, we developed BC Data ScoutTM, a cohort browser. Objectives and Approach We developed a cohort browser service to provide information to researchers planning a study using MOH data. The objective was to create a tool that is simple to use, provides quick results and is free to users to encourage its use. A better understanding of the data available can improve study quality and expand the user-base by giving researchers access to information not previously available during the planning stages. The tool will be evaluated by examining the number of requests received and a user satisfaction survey. Plans are in place to expand into additional data sources and extend query sophistication. Results The BC Data ScoutTM online tool provides cohort information in the form of highly aggregated, approximate results to researchers planning a study. It was developed by the MOH, the BC SUPPORT Unit and Population Data BC (PopData) and was launched in February 2018. The service is delivered by PopData. BC Data ScoutTM offers province-wide information for query, is accessible to a wide group of eligible researchers, and has data availability from the year 2000 onwards. Four types of MOH data are available for query: hospital data; physician data; pharmaceutical data; and demographics. In addition to determining study feasibility, the aggregate reports also help to further refine a full data access request and provide enough information to complete and strengthen a funding application. Conclusion/Implications BC Data ScoutTM will be beneficial for researchers planning to request data. This preliminary information may increase the chances of meaningful research studies to obtain funding, and the production of relevant, high-quality research results. BC will be among the first jurisdictions across Canada to offer this type of feasibility service.